Agent-based ubiquitous computing - Carbo, Javier (Atlantis Ambient and Pervasive Intelligence, 2010)
Ubiquitous computing names the third wave in computing, where the personal computing era appears when technologyrecedesinto the backgroundof our lives. The widespread use of new mobile technology implementing wireless communicationssuch as personal digital assistants (PDAs) and smart phones enables a new type of advanced applications. In the past years, the main focus of research in mobile services has a imedatthe any time-anywhere principle (ubiquitous computing). However, there is more to it. The increasing demand for distributed problem solving led to the development of multi-agent systems. The latter are formed from a collection of independent software entities whose collective skills can be applied in complex and real-time domains. The target of such systems is to demonstrate how goal directed, robust and optimal behavior canarise from interactions between individual autonomous intelligent software agents. These software entities exhibit characteristics like autonomy, responsiveness, pro-activeness and social ability. Their functionality and effectiveness has proven to be highly depended on the design and development and the application domain. In fact, in several cases, the design and developmentof effective services should take into account the characteristics of the context from which a service is requested. Contextis the set of suitable environmentalstates and settings concerninga user, which are relevant for a situation sensitive application in the process of adapting the services and information offered to the user. Agent technology seems to be the right technology to offer the possibility of exploring the dynamic context of the user in order to provideadded-value services or to execute more and complex tasks. Solving conflicts in agent-based ubiquitous computing systems: a proposal based on argumentation - Mixed Reality Agent (MiRA) Chameleons - A generic architecture for human-aware ambient computing - e-Assistance support by intelligent agents over MANETs - The ActiveMetadata framework - Coalition of surveillance agents. Cooperative fusion improvement in surveillance systems - Designing a distributed context-aware multi-agent system - Agent-based context-aware service in a smart space - An agent based prototype for optimizing power plant operation - IUMELA: Intelligent Ubiquitous Modular Education Learning Assistant in third leveleducation.